2012
DOI: 10.1002/chem.201202382
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated 3‐Heteroarylcoumarins and Their Use in Fluorescence Microscopy and Nanoscopy

Abstract: Photostable and bright fluorescent dyes with large Stokes shifts are widely used as markers in far-field optical microscopy, but the variety of useful dyes is limited. The present study introduces new 3-heteroaryl coumarins decorated with a primary phosphate group (OP(O)(OH)(2)) attached to C-4 in 2,2,4-trimethyl-1,2-dihydroquinoline fragment fused with the coumarin fluorophore. The general synthetic route is based on the Suzuki reaction of 3-bromocoumarines with hetarylboronic acids followed by oxidation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 54 publications
1
65
0
3
Order By: Relevance
“…The extended conjugation in the dihydroquinoline moiety and the 3-pyridyl substituent also contribute to the useful spectral properties observed with this dye. 43 …”
Section: Coumarinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extended conjugation in the dihydroquinoline moiety and the 3-pyridyl substituent also contribute to the useful spectral properties observed with this dye. 43 …”
Section: Coumarinsmentioning
confidence: 99%
“…46 This reaction can be performed on highly functionalized molecules such as the reaction of dihydroquinoline 15 and 2-pyridylacetic acid 16 to afford highly soluble coumarin 10 . 43 …”
Section: Coumarinsmentioning
confidence: 99%
“…[17] Compounds 7-H,SO 3 H,Y are readily available by sulfonation of the corresponding precursors 7-H,H,Y (Y = H, CO 2 Et), which, in turn, can be easily synthesized from phenol 5-H,TBDMS [18] (Scheme 4; TBDMS = tert-butyldimethylsilyl). The appropriate protecting groups should be compatible with the conditions of the diazoketone synthesis.…”
Section: ][9h]xanthen-3-one Fragmentmentioning
confidence: 99%
“…Its synthesis is depicted in Scheme . Coumarin 343 is a representative of rigidified 7‐aminocoumarins, characterized by their bathochromic shift of both absorption and emission . It has been reported that coumarin 343 gives a high fluorescence quantum yield (ϕ = 0.7) in water and also in organic solvents, i.e., ethanol (ϕ = 0.63) .…”
Section: Resultsmentioning
confidence: 99%
“…Miscellaneous types of fluorophores have been employed for manifold purposes. Besides BODIPY (boron‐dipyrromethene) and fluorescein derivatives, coumarins represent a widely used class of fluorescent dyes and are valued for their small molecular size and large Stokes shifts . Structure–fluorescence relationships of the coumarin chemotype revealed high fluorescence as a result of the introduction of an electron‐donating substituent at the 7‐position.…”
Section: Introductionmentioning
confidence: 99%